Longitudinal Relations Between Self-Defining Memories and Self-Esteem: Mediating Roles of Meaning-Making and Memory Function. (March 2018) - Liao, Hsiao-Wen; Bluck, Susan; Westerhof, Gerben J.
The present study examinesHsiao-Wen Liao is now at the Department of Psychology, Stanford University, CA, USA. the role of self-defining memories in predicting self-esteem using a 1-year longitudinal design with an adult lifespan sample ( N = 1, 216; age range 18–92; M age = 49.52; SD age = 17.25). The interplay between narrators' personality at the life story level and two social-cognitive processes, meaning-making and functional memory use, is investigated. Participants provided three self-defining memories, and their personality positivity was assessed in terms of the ratio of positive-to-all memories. Memory narratives were reliably coded for meaning-making, and participants reported the extent to which they use each remembered event to serve adaptive functions. One year later, participants completed a measure of self-esteem. Personality positivity at Time 1 predicts greater self-esteem at Time 2. The effect of personality positivity occurs, however, completely through creating positive meaning and using memories functionally. The findings contribute to the literature on narrative identity and autobiographical memory by delineating how memory processes relate to self-regulation over time. The relative roles of personality and social-cognitive processes in autobiographical narratives in linking to self-esteem are discussed.